7.3 POLYGENIC RISK FOR SCHIZOPHRENIA MODERATES THE INFLUENCE OF CHILDHOOD ADVERSITY ON DAILY-LIFE EMOTIONAL DYSREGULATION AND PSYCHOSIS PRONENESS. (9th April 2019) - Pries, Lotta-Katrin; Klingenberg, Boris; Menne-Lothmann, Claudia; Decoster, Jeroen; Winkel, Ruud van; Collip, Dina; Delespaul, Philippe; Hert, Marc De; Derom, Catherine; Thiery, Evert; Jacobs, Nele; Wichers, Marieke; et al.
Abstract: Background: Emotional dysregulation and subtle psychosis expression mark the earliest manifestation of psychopathology. Furthermore, using Ecological Momentary Assessment (EMA), studies indicate that emotional and psychotic reactivity to daily-life stressors are associated with psychosis expression in individuals at varying clinical stages (e.g. service users, clinical high-risk, or first episode psychosis). The question arises how fluctuations of those momentary mental states persist and transit into more distinct clinical outcomes (e.g. psychotic spectrum disorder). In this context, studies using the EMA previously showed that environmental vulnerabilities (i.e. childhood adversities) are consistently associated with increased and persistent emotional and psychotic reactivity. However, the effects of molecular genetic liability for schizophrenia on this association have not been investigated. Therefore, in the largest EMA study to date, we aim to test whether polygenic risk for schizophrenia (PRS) interacts with childhood adversity on momentary mental states (negative affect, positive affect and subtle psychosis expression). Methods: A prospective population-based twin cohort from multi-birth registry in Flanders, Belgium, collected data from April 2010 to April 2014 in the first wave of the TwinssCan project. The study sample included 593 adolescents and young adults between the ages of 15 and 35 years. Childhood Adversity was assessed using the Childhood Trauma Questionnaire. Momentary mental state domains (negative affect, positive affect and subtle psychosis expression) were measured using EMA. Emotional states were the mean sore of items concerning negative affect (I feel anxious, lonely, down, insecure and irritated) and positive affect (I feel cheerful, satisfied, relaxed, and globally feeling well, respectively). Subtle psychosis expression was the mean score of items concerning psychotic-like experiences (suspiciousness, being afraid of losing control, racing thoughts, pervasive thoughts, and difficulties to express thoughts). Genetic risk was estimated by PRS, which was trained on the latest Psychiatric Genetics Consortium schizophrenia meta-analysis, adjusted for the first 2 population principal components. The analyses were conducted using multilevel tobit regression with age and sex included as a priori covariates. Results: Exposure to childhood adversity was associated with increased negative affect (b = 0.13, 95% CI 0.07 to 0.19, P < 0.001), decreased positive affect (b = -0.12, 95% CI 0.17 to -0.06, P < 0.001), and increased subtle psychosis expression (b = 0.18, 95% CI 0.10 to 0.26, P < 0.001). PRS was only associated with increased positive affect (b = 0.08, 95% CI 0.03 to 0.14, P < 0.001), and no gene–environment correlation was detected (b = -0.01, 95% CI -0.03 to 0.02, P = 0.676). PRS moderated the association of childhood adversity with all momentary mental states, negative affect (b = 0.07, 95% CI 0.01 to 0.13, P = 0.013), positive affect (b = -0.05, 95% CI -0.10 to -0.00, P = 0.043), and subtle psychosis expression (b = 0.11, 95% CI 0.03 to 0.19, P = 0.007). Conclusions: PRS moderated the influence of childhood adversity on all emotional regulation and subtle psychosis expression. This is in line with hypothesis arguing that the experience of early-life stressors during critical neurodevelopmental periods may lead to the imbalance of stress mechanisms and subsequently cause emotional and behavioral problems. Genetic vulnerability and early-lifetime stressors pleiotropically co-participate in driving emotional dysregulation and psychosis proneness.